Time, cause of early neonatal death, and its predictors among neonates admitted to neonatal intensive care units at Bahir Dar City public hospitals, northwest Ethiopia: a prospective follow-up study - Abraham Dessie Gessesse; Minyichil Birhanu Belete; Fikir Tadesse (Frontiers Media S.A., 2024)
BackgroundGlobally, 75% of neonatal deaths occur during the first weeks of life and more than 43% of deaths are covered by sub-Saharan Africa. Health-related policymakers and decision-makers need to use evidence-based treatments to reduce the time to early neonatal death and associated predictors. However, there are limited studies on median survival time, cause, incidence, and predictors in the study area as well as the country. Therefore, the aim of the present study was to assess time, the cause of early neonatal death, and its predictors among neonates admitted to neonatal intensive care units at Bahir Dar City public hospitals in northwest Ethiopia.MethodsAn institution-based prospective follow-up study design was conducted among 387 early neonates selected by systematic sampling between 22 February and 22 April 2023. Statistical software, Epi Data version 4.6 and Stata version 14, was used for entry and analysis, respectively. Proportional hazard assumption and model fitness were checked by the Schoenfeld residual test and the Cox-Snell residual test, respectively. Descriptive statistics, the Kaplan-Meier curve, and the life table were used to describe variables. The Cox regression analysis model was fitted to identify the predictors of early neonatal death.ResultDuring the follow-up time, 59 (15.25%) early neonates died, with an incidence of 31.79 per 1,000 early neonate days [95% confidence interval (CI): 0.024-0.041]. The leading causes of early neonatal death were prematurity complications, asphyxia, sepsis, meconium aspiration syndrome, and necrotizing enterocolitis. The mean survival time was 2.72 days. Being born from a multigravida mother [adjusted hazard ratio (AHR) 4.34; 95% CI: 1.63-11.55], a grand multigravida mother (AHR 3.50; 95% CI: 1.12-10.95), respiratory distress syndrome (AHR 2.60; 95% CI: 1.03-6.58), birth asphyxia (AHR 7.51; 95% CI: 2.30-24.51), a small gestational age (AHR 2.05; 95% CI: 1.08-4.92), and being unable to exclusively breastfeed (AHR 3.46; 95% CI: 1.52-7.88) were significantly associated predictors for time to early neonatal death.Conclusion and recommendationsThe incidence of early neonatal death was high, and the mean survival time was 2.72 days. Gravidity, respiratory distress syndrome, birth asphyxia, and being unable to exclusively breastfeed were identified as predictors of early neonatal death. Therefore, future research will consist of long-term prospective follow-up studies at a multicenter, nationwide level.